2011
DOI: 10.1002/fut.20521
|View full text |Cite
|
Sign up to set email alerts
|

Equity volatility, bond yields, and yield spreads

Abstract: This study examines the impact of implied and contemporaneous equity market volatility on Treasury yields, corporate bond yields, and yield spreads over Treasuries. The CBOE VIX is the measure of implied volatility, and the measure of contemporaneous volatility is constructed using intraday squared S&P 500 returns. We find that bond yields and spreads respond to changes in equity market volatility in a manner consistent with a flight-to-quality effect. Both shortand long-term Treasury yields fall in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…The second strand is research focusing explicitly on uncertainty and its relation to conventional assets such as stocks and bonds and to commodities. For example, Jubinski and Lipton (2012) show that the negative association between the VIX and yields on treasury and investment-grade bonds is in line with the flight-to-safety effect, confirming the view of Thomas (2015).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…The second strand is research focusing explicitly on uncertainty and its relation to conventional assets such as stocks and bonds and to commodities. For example, Jubinski and Lipton (2012) show that the negative association between the VIX and yields on treasury and investment-grade bonds is in line with the flight-to-safety effect, confirming the view of Thomas (2015).…”
Section: Introductionsupporting
confidence: 74%
“…Notably, an increase in the VIX generally results in 'flights to safety' (Thomas, 2015). For example, Jubinski and Lipton (2012) highlight the negative correlation between the VIX and treasury and investment grade bond yields. This means that yields fall in response to increases in implied volatility, suggesting that bond price increases as equity decreases.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whereas for the stock markets in Egypt, Oman, Saudi Arabia, and Kuwait, Abdelaziz, Chortareas, & Cipollini (2008) discovered a relationship of oil with the capital markets. For the US capital markets, Jubinski & Lipton (2013) concluded that the world oil price change gives significant effect on S&P500 Index return. Is the ASEAN region, Hersugondo et al (2015) conducted a research on the effect of the change of world oil price to the stock market return in several countries in ASEAN region.…”
Section: |mentioning
confidence: 99%
“…Fleming, Kirby, and Ostdiek (1998) and Kodres and Pritsker (2002) suggest cross-asset-class effects tied to hedging and portfolio rebalancing. Pricing effects linking the stock and bond markets have been attributed to flight-toquality/flight-from-quality (FTQ/FFQ), where some investors (presumably) switch between riskier stocks and safer Treasuries as risk perceptions change Sun, 2005, 2007;Underwood, 2009;Baele, Bekaert, and Inghelbrecht, 2010;BenRaphael, Kandel, and Wohl, 2012;Jubinski and Lipton, 2012;Bansal, Connolly, and Stivers, 2014). 3 Chordia, Sarkar, and Subrahmanyam (2005) find that innovations to stock volatility forecast an increase in bond bid-ask spreads.…”
Section: Introductionmentioning
confidence: 99%